ANALISA PENILAIAN KELAYAKAN JAMINAN DALAM PENGAMBILAN KEPUTUSAN KREDIT UMKM PADA LEMBAGA KEUANGAN DI INDONESIA - Aris Kurniawan (Institut Teknologi dan Bisnis Dewantara, 2020)
The research tries to explain credit guarantees that are generally accepted by banks, especially in the MSME credit segment. The author tries to explain best practices related to credit guarantees, credit guarantee assessment and, types of guarantees that are generally avoided by banks. The object in this study is a bank that serves financing or credit, especially the UMKM segment, both government banks and private banks. The research method used was descriptive qualitative. Sources of data used are data that the authors obtained from the bank's official website which is the object of research. In addition, the author also collects brochures from several banks, other supporting data is the credit policy guidebook that the author has where the author has worked at several of these banks. To complete the information and data, the author also conducted interviews with several marketing banks. The results of the discussion in this study explain the types of collateral generally accepted by banks are land and buildings, vacant land, kiosks, motorized vehicles 2 and 4 and deposits. For LTV (Loan To Value) or the ratio of the amount of the loan compared to the guarantee provided, among others, a maximum of 70-80% vacant land, 80% maximum land and buildings, 60-70% maximum motorized vehicles and a maximum deposit of 90%. The guarantees generally avoided by banks for land and buildings are guarantees intended for green lines, road widths less than one meter, under high voltage electricity, carried by heavy currents, land in dispute, land and buildings designated and used for public and religious facilities etc .